Towards Evidence-Based Talent Identification in Youth Volleyball: Designing a Dual-Dimensional Evaluation Tool - Faihan, Amer Mishaal (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The process of talent identification in youth volleyball is a complicated task because there are no effective and evidence-based instruments to combine technical and physical aspects of a player performance. The proposed study attempts to design, develop, and validate a Dual-Dimensional Evaluation Tool in order to increase the accuracy of the prediction and objectivity of talent identification processes. A cross-sectional and longitudinal observation and quantitative research design with 100-300 youth volleyball players (under age 18 years) was used sampling the youth players in schools, academies and volleyball clubs. The tool will involve two major dimensions; namely Physical Metrics (e.g., height, reach, sprint speed, agility, and jump performance) and Technical Skill Metrics (e.g., serve accuracy, setting precision, defensive digs, spike targeting, and game intelligence). Data were collected using standardized protocols on the one hand using trained assessors and on the other through video validation of skill-based assessment. Evidence of support was developed through exploratory factor analysis (EFA) as scale validation to support the two-factor structure, Cronbach alpha as a reminder of internal consistency, inter-rater reliability concerning the subjective ratings and regression modeling in regards to the predictive capacity of the scores of future performance outcomes. Test difficulty and scoring were refined on the basis of preliminary pilot testing of 30 participants. The last scoring system resulted in a normalised Talent Index Score that was based 60 percent technical performance, and 40 percent physical performance. The findings proved to be highly reliable (alpha > 0.85) and articulately distinguished into dimensions and correlations were significant between tool scores and future competitive success. The suggested assessment protocol provides coaches and talent scouts with a valid and flexible platform to employ a consistent and methodical process of recognizing potential youth volleyball players and advising the long-term athlete development schemes.